Language Politeness in The 12.12 Phenomenon E-Commerce in The Era of Industrial Revolution 4.0 - Atikah, Nurul; Anggraeny, Niya; Indriyani (Universitas Swadaya Gunung Jati, 2024)
The purpose of the research to describe the maxims in the speech of the e-commerce Shopee and Lazada in the phenomenon 12.12. This research is focused on the politeness in language that related to the maxims including tact, generosity, approbation, modesty, agreement, and sympathy. The researcher used descriptive qualitative as the research method for this research. The data source of the research was the speech between participants or customers of the 12.12 phenomenon with Shopee and Lazada admins in Instagram social media. The data of this research are 1.253 words or comments. The details are 692 in the Shopee comments column and 561 in the Lazada comments column. The data was chosen based on the focus of topics related to the use of shopping vouchers, free shipping costs, ect. The data were gained through reading and note taking. The data analysis technique conducted by researcher through namely data reduction, data presentation and verification. The results of the analysis show that politeness of language in the 12.12 e-commerce phenomenon Shopee and Lazada as an effort to maintain harmony by maximizing and prioritizing the benefits of other parties, namely customers. This is evidenced by the tact maxim which dominates the speech of Shopee and Lazada staff when interacting with other parties.